(untitled) - Hallman, G Victor (New York, 1983)
This book helps you explore your personal financial options - choose and use the various finacial tools ( stocks, bonds, real estate, trusts, etc. ) you can employ to accumulate and protect capital - and achieve your financial objectives at lowest cost. It covers tax planning, health, property, and liability insurance, ...
Keywords: Finance, personal